POLA KOMUNIKASI GURU DAN SISWA SMPN 5 KOTA SUKABUMI DALAM PENDIDIKAN SEKS - Huda Febriyani (PT. Naureen Digital Education, 2023)
The rise of cases of promiscuity related to pre-marital sex by teenagers is caused by a lack of education about adolescent sex education which is still considered taboo to discuss. This study aims to find out the communication patterns used by teachers toward students of SMPN 5 Kota Sukabumi in delivering sex education. This research is a type of qualitative descriptive research with an ethnographic communication approach used to achieve the research objectives. The research data was obtained through interviews conducted with students aged 13-14 years, as well as teachers aged 30-45 using recording and note-taking techniques. From the results of the study, data was obtained that the delivery of sex education at SMPN 5 Sukabumi City had been carried out through integrated subjects that were in accordance with the curriculum and delivered with persuasive communication patterns so that students could ask questions broadly and understand well. In conclusion, sex education at SMPN 5 Kota Sukabumi has been delivered with good and interesting communication patterns.